Active approach to forming scientific and research competence among future environmentalists - Soloshych, I (Problems of Engineer-Pedagogical Education, 2019)
The article deals with the issues of implementingthe active approach to the formation of scientific and research competence among future environmentalists, which contributes to creating conditions for the disclosure and realization of the individual research potential of each student. The study clarifies the definition of the concepts of "research competence", "activity approach", "research activity", "educational and research activity". Four stages of the research process are identified (statement of the research problem, research planning, implementation of research methods, evaluation of research results), as well as the division of research competences into the corresponding subcomponents of the above-named phases such ascognitive, abductive, argumentative and verification ones. Students’ readiness for researchwork is considered together with the motivational, orientational, activitybased and reflexive components. The principles on which scientific research is based includeits scientific nature, systematicness, accessibility, awarenessabout its purposefulness, integrity, freedom of choice, polylogical knowledge, activity mediation, individualization, subjectivity, and diversification. The research qualities of an individualare asfollows: motivational (characterizing the attitude of an individual to the research activity); operational (including mental techniques and operations used by an individual in research activities); organizational (referring to the ability and skills of a specialist to apply methods of self-organization in research activities); communicative (which involves the ability of a specialist to cooperate). It is determined that strengthening of the research aspect of the educational and cognitive activity of future environmental specialists in the process of specializedtraining and the transition from informative to active methods and forms of learning with the inclusion of the problem-solving elements into students’ educational and research activitiesguarantee intellectualization of the educational process.